Efektivitas Pembimbingan Kemasyarakatan Terhadap Anak Pelaku Pelecehan Seksual di Balai Pemasyarakatan Kelas I Denpasar - Made Ryan Permana Putra; I Made Sepud; Ketut Adi Wirawan (Warmadewa Press, 2024)
Sexual harassment is a criminal offense that can cause harm in the form of trauma or embarrassment to the family or society. Children as perpetrators of criminal acts of sexual harassment who are still underage, need to receive serious attention from all walks of life.This is done to improve the mindset of the perpetrators, teach the perpetrators to do good and help the perpetrators meet the prevailing standard of living. This study uses empirical legal research methods. There are internal, external, and other factors that contribute to children committing sexual harassment offenses. External factors include emotional power and age, external factors consist of education, environment, alcohol and drugs, economy, and the internet. Meanwhile, other factors that support children to commit crimes of sexual harassment are children's low understanding of religion and the absence of parental oversight. The study's findings indicate that, in accordance with the applicable laws and regulations, social counseling for child sexual harassment perpetrators has been working well and effectively. The absence demonstrates this repetition of criminal acts or recidivism. This happens because the process of guiding and supervising children who commit crimes of sexual harassment by social counselors has been running according to the rules that apply.